2021
DOI: 10.3389/fcimb.2021.703126
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Gut Microbiota in Chronic Spontaneous Urticaria and Symptomatic Dermographism

Abstract: BackgroundChronic urticaria (CU) is a chronic inflammatory skin disease associated with Th2 immune response. The two most common subtypes of CU, i.e., chronic spontaneous urticaria and symptomatic dermographism (CSD), often coexist. However, the pathogenesis of CSD is still unclear. Gut microbiota plays an important role in immune-related inflammatory diseases. The purpose of this study was to explore the correlation between gut microbiota and CSD.MethodsA case-control study was conducted on CSD patients as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 56 publications
8
29
1
1
Order By: Relevance
“…α-diversity was used to compare the diversity within a sample, and we found that the two groups of microorganisms were statistically different in richness (Chao1 and Observed species) and diversity (Shannon), but not different in evenness (Pielou’s evenness). The α-diversity of the CSU was generally higher than that of the control group, which contradicted earlier research ( Lu et al., 2019 ; Wang et al., 2020 ; Wang et al., 2021 ; Liu et al., 2021 ; Yüksekal et al., 2022 ). Some studies reported that there were significant differences in α-diversity, and the species diversity of chronic urticaria group decreased ( Lu et al., 2019 ; Wang et al., 2020 ); other studies found no significant difference in α-diversity between CSU patients and controls ( Zhang et al., 2021 ; Wang et al., 2021 ).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…α-diversity was used to compare the diversity within a sample, and we found that the two groups of microorganisms were statistically different in richness (Chao1 and Observed species) and diversity (Shannon), but not different in evenness (Pielou’s evenness). The α-diversity of the CSU was generally higher than that of the control group, which contradicted earlier research ( Lu et al., 2019 ; Wang et al., 2020 ; Wang et al., 2021 ; Liu et al., 2021 ; Yüksekal et al., 2022 ). Some studies reported that there were significant differences in α-diversity, and the species diversity of chronic urticaria group decreased ( Lu et al., 2019 ; Wang et al., 2020 ); other studies found no significant difference in α-diversity between CSU patients and controls ( Zhang et al., 2021 ; Wang et al., 2021 ).…”
Section: Discussioncontrasting
confidence: 90%
“…This result may be controversial, and we think that it may be related to factors such as sample size, the geographical location of the subjects, eating habits, and research methods. While β-diversity was used to assess diversity across various samples, there was a significant difference between the CSU and NCs group, which is consistent with previous studies ( Lu et al., 2019 ; Wang et al., 2020 ; Wang et al., 2021 ; Liu et al., 2021 ; Zhang et al., 2021 ; Yüksekal et al., 2022 ). Composition analysis of the two groups of samples showed that the relative abundance of Firmicutes increased in the CSU group, while the relative abundance of Bacteroidetes and Proteobacteria decreased, which was similar to the study by Wang et al ( Wang et al., 2021 ), but different from the decreased abundance of Firmicutes in the study by Wang et al ( Wang et al., 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…Immunologic dysfunction and thrombophilia are known key factors in the pathogenesis of SAB (Liu et al, 2021a). A previous study showed that the relative abundance of Actinomyces and Subdoligranulum is closely related to multiple autoimmune diseases, including systemic lupus erythematosus and chronic spontaneous urticaria, suggesting that these bacteria play an important role in the host immune response (Chen B. D. et al, 2021;Liu et al, 2021). The protective effect of Lactococcus on SAB was likely due to lactic acid bacteria reducing autoimmunity and recovering immune homeostasis (Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota involved in various diseases is gradually revealed. Gut microbiota has even become a biomarker for the treatment and diagnosis of some complex diseases, such as bipolar disorder ( 12 ), chronic spontaneous urticaria, and symptomatic dermographism ( 13 ). As summarized in our previous review, the impact of the gut microbiota on host health is mainly achieved through microbial metabolites ( 14 ).…”
Section: Introductionmentioning
confidence: 99%